2019
DOI: 10.1186/s13033-018-0257-4
|View full text |Cite
|
Sign up to set email alerts
|

Stress, anxiety and depression in clinical nurses in Vietnam: a cross-sectional survey and cluster analysis

Abstract: BackgroundHospital nurses are exposed to various work-related factors that may be associated with increased risk of developing different mental disorders. Empirical evidence on the prevalence and correlates of individual mental health problems such as stress, anxiety and depression is widely reported, while a combined pattern of these conditions is unknown. This study aims to examine the co-occurrence of stress, anxiety and depression among clinical nurses, and to explore socio-demographic characteristics of, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
5
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 47 publications
2
59
5
13
Order By: Relevance
“…Nurses expend much effort in caring for their patients and frequently experience related psychological health problems (Gong et al 2014;Tran et al 2019). Such health problem can negatively impact quality of patient care (Maharaj et al 2019a) and increase turnover intention (Sasso et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses expend much effort in caring for their patients and frequently experience related psychological health problems (Gong et al 2014;Tran et al 2019). Such health problem can negatively impact quality of patient care (Maharaj et al 2019a) and increase turnover intention (Sasso et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In Vietnam, research on occupational health is still limited. In the population of nurses, there was only a few studies regarding issues related to occupational exposures (exposure to blood and secretions, occupational tuberculosis, or radiation …) [17] or mental health problems (stress, anxiety, and depression) [18]. For MSDs, there were two existing studies published to date: the first one by Kieu et al in 2016, conducted in over 300 nurses working at a regional hospital, having demonstrated a high prevalence of MSDs (81%) during the past 12 months [19]; and the second one is our study which was carried out on all nurses working at all district hospitals in Haiphong city where the general prevalence was 74.7 [20].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted by Yang et al (2019) in China showed that 97% of nurses suffered from at least one workrelated musculoskeletal problem with 80.91% reporting low back pain, 78.6% reporting neck pain, and 70.4% reporting shoulder pain [9]. With regards to mental health, reports from around the world have estimated a prevalence of mental health problems among nurses of 45.3% [3] and a prevalence of emotional exhaustion of 26% in Brazil [43], 30% in the USA [19], 43% in Spain [21], and 50% in Turkey [20]. Over half of the RNs in our sample reported the presence of mental disorders and/or high emotional exhaustion, highlighting a higher prevalence of these important problems among Lebanese nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, accumulated data show that nursing is a demanding and stressful profession [1][2][3]. Nurses work in complex environments, on variable and long rotating shifts, and are exposed to a variety of occupational risks and accidents [4][5][6].…”
Section: Introductionmentioning
confidence: 99%